MEDICAL, BIOLOGICAL, AND SOCIO-HYGIENIC RISK FACTORS IN THE DEVELOPMENT OF BREAST TUMOR DISEASES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The results of our study demonstrated that the increased risk of developing benign breast tumor diseases is closely associated with medical and biological factors. The most significant factors include: late onset of menarche (ages 15–17); delayed childbirth; artificially terminated pregnancies; lack of breastfeeding or short-term breastfeeding; the presence of comorbidities (inflammatory diseases of the genital organs, liver, gallbladder, and bile ducts, as well as various thyroid diseases); irregular sexual activity; excessive body mass index (BMI); genetic predisposition; and breast trauma. Early identification of risk factors enables the effective organization of preventive measures to reduce the incidence of breast tumor diseases.